Molecular Luminescence of White Carbon. Issue 12 (23rd January 2017) - Xiao, Jun; Li, Jiling; Yang, Guowei
Abstract : Four‐color emission modulated by the molecular chain length from white carbon (carbyne crystals) is observed. It is also established that a carbyne molecule with four carbon atoms is the basic unit or building block to construct carbyne crystals, where the chain length of the carbyne molecule in the synthesized carbyne crystals follows the rule of 4 n ( n = 1, 2, 3, …).